The effect of formal and informal institutions on poverty reduction - Bugaje, Idris Bashir; Abd Rahman, Azmawani; Said, Rusmawati; Jo, Ann Ho; Chindo, Sulaiman (Exeliq Publishing, 2018)
Despite meaningful achievement with regards to poverty, it is disconcerting that about 1.5 billion people across the globe are multi-dimensionally poor and over 900 million are vulnerable and might be poor in no distance future. Although having good institution is a prerequisite of the workings of socio-economic conditions of any country, studies on institution focus more on economic growth, happiness, the welfare of the people and others. This paper examined the effect of entrepreneurship-related institutional factors in reducing poverty in 18 selected countries. The study considering the panel nature of the data used adopted generalized method of moments (GMM) over other conventional panel methods. The results show that poverty headcount, poverty gap, squared poverty gap, and watts index are negatively and significantly related to government support and policies, and culture and social norms. Meanwhile, poverty headcount is positively but insignificantly related to governmental programs and taxes and bureaucracy. However, poverty gap, squared poverty gap, and watts index are negatively related to governmental programs and taxes and bureaucracy are found to have a negative and significant effect on squared poverty gap. The study recommends that government should strengthen its policies supporting entrepreneurship by making policies that are linked towards supporting entrepreneurship and by invariably integrating the informal institutions as they are effective in reducing poverty. Entrepreneurial programs should be targeted at the people who are extremely poor so as to have the desired effect while government should reduce taxes as well as make market entry easy.